758. Tuberculosis Recurrence in New York City: A Retrospective Study - McPherson, Tristan (Open Forum Infect Dis, 2018)
BACKGROUND: Tuberculosis (TB) recurrence has been difficult to determine due to diverse definitions. Without knowledge of recurrence rates or associated risk factors, patients with highest likelihood of recurrence may not be identified, contributing to continued morbidity and disease transmission. We aimed to determine the recurrence rate for TB cases, associated clinical findings and patient characteristics. METHODS: We conducted a retrospective study evaluating 7,755 New York City TB cases from 2005 to 2014 for recurrence after appropriate treatment completion through 2017. Demographic, clinical, drug susceptibility testing (DST), and genotype data were collected during routine care. Adjusted odds ratios (aOR) were calculated to estimate associated risk factors for recurrence. RESULTS: A total of 73 cases were identified with ≥ one recurrence, a rate of 0.9%. Median time to recurrence after treatment was 516 days (IQR 165–1,256). In univariate analysis, pulmonary or combination of pulmonary and extrapulmonary disease, human immunodeficiency virus (HIV) infection, culture positive disease, alcohol abuse, intravenous drug use, and homelessness in the 12 months prior to diagnosis were associated with recurrence (P < 0.05). In adjusted analysis, HIV infection (aOR 2.04 95% CI 1.13–3.67), pulmonary disease (aOR 9.03 95% CI 2.19–37.12), and having both pulmonary and extrapulmonary disease (aOR 17.19 95% CI 4.0–74.0) were independently associated with recurrence. Of 67 cases with positive culture and DST, 10 had additional drug resistance and 14 had new disease sites. Among 36 cases with complete genotyping information, data suggested relapse in 27 (75%) cases and re-infection in two (5.5%). Re-infection could not be ruled out in seven (19%) cases. CONCLUSION: The recurrence rate for this period was lower than expected compared with other studies. HIV infection continues to be associated with recurrence despite availability of effective antiviral medication. Those with pulmonary or disseminated TB were more likely to have recurrence compared with only extrapulmonary TB. A notable number of recurrent cases demonstrated new drug resistance or disease manifestations, which should be considered in later treatment regimens and follow-up evaluation. DISCLOSURES: All authors: No reported disclosures.